2011
DOI: 10.1371/journal.pone.0023517
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Specific DNA Endonuclease Mus81/Eme1 Generates DNA Damage Caused by Chk1 Inactivation

Abstract: The DNA-damage checkpoint kinase Chk1 is essential in higher eukaryotes due to its role in maintaining genome stability in proliferating cells. CHK1 gene deletion is embryonically lethal, and Chk1 inhibition in replicating cells causes cell-cycle defects that eventually lead to perturbed replication and replication-fork collapse, thus generating endogenous DNA damage. What is the cause of replication-fork collapse when Chk1 is inactivated, however, remains poorly understood. Here, we show that generation of DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 29 publications
7
114
2
Order By: Relevance
“…Although it is not clearly essential for fork collapse in all cell types, the Mus81-Eme1 complex in Schizosaccharomyces pombe plays a crucial role in DSB generation at stalled replication forks (Froget et al 2008), and a similar relationship has been observed in mammalian cells when CHK1 is inhibited (Forment et al 2011). These findings in aggregate suggest that PLK1 could play an active facilitative role in replication fork collapse at the level of both the replisome and cleaving aberrant fork structures.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Although it is not clearly essential for fork collapse in all cell types, the Mus81-Eme1 complex in Schizosaccharomyces pombe plays a crucial role in DSB generation at stalled replication forks (Froget et al 2008), and a similar relationship has been observed in mammalian cells when CHK1 is inhibited (Forment et al 2011). These findings in aggregate suggest that PLK1 could play an active facilitative role in replication fork collapse at the level of both the replisome and cleaving aberrant fork structures.…”
mentioning
confidence: 71%
“…The SLX4-endonuclease complex has previously been implicated as a mediator of replication fork collapse, particularly in cooperation with the MUS81-EME1 complex (Froget et al 2008;Forment et al 2011;Matos et al 2011;Gallo-Fernandez et al 2012;Munoz-Galvan et al 2012;Schwartz et al 2012;Szakal and Branzei 2013). To examine the involvement of this complex in the DSBs generated upon fork stalling in ATR-deficient cells, Crelox conditional SLX4 cells were used to delete Slx4 and determine the effect of its absence on DSB generation following ATR inhibition and fork stalling.…”
Section: Rnf4 and Plk1 Are Required For Slx4-dependent Dsb Formation mentioning
confidence: 99%
“…4B). The MUS81 structurespecific endonuclease generates DSBs during persistent exposure to replication stress agents or in response to silencing or inhibition of replication fork repair proteins such as WRN, SMARCAL1, and CHK1 (Hanada et al 2007;Franchitto et al 2008;Forment et al 2011;Betous et al 2012). Therefore, we tested whether siRNA depletion of MUS81 affects DSB formation in HU/ATRi-treated cells.…”
Section: Atr Inhibition Causes Nascent-strand Ssdna Formationmentioning
confidence: 99%
“…The massive amount of DNA breakage is likely mediated by DNA endonuclease activity, and recent studies suggest that this is mediated by the endonuclease MUS81 (12,14,15). Notably, the mechanisms by which oncogenes or inhibition of checkpoint kinases can lead to endonuclease-mediated DNA breakage are poorly understood.…”
mentioning
confidence: 99%